Targeting Tumor-Associated Macrophages in Cancer. Issue 4 (April 2019) - Pathria, Paulina; Louis, Tiani L.; Varner, Judith A.
Abstract : Macrophages are phagocytes that serve as a first line of defense against pathogenic insults to tissues. These innate immune cells mount proinflammatory responses to pathogens and repair damaged tissues. However, tumor-associated macrophages (TAMs) express cytokines and chemokines that can suppress antitumor immunity and promote tumor progression. Preclinical studies have identified crucial pathways regulating the recruitment, polarization, and metabolism of TAMs during tumor progression. Moreover, novel therapeutics targeting these pathways can indirectly stimulate cytotoxic T cell activation and recruitment, and synergize with checkpoint inhibitors, chemotherapy and/or radiation therapy in preclinical studies. Thus, clinical trials with therapeutic agents that promote phagocytosis or suppress survival, proliferation, trafficking, or polarization of TAMs are currently underway. These early results offer the promise of improved cancer outcomes. Highlights: TAMs express cytokines and enzymes that can suppress T cell recruitment and activation, thereby promoting resistance to immune checkpoint inhibition. Bone-marrow-derived and tissue-resident TAMs each contribute to TAM overall content, and both can promote tumor immunosuppression. In preclinical mouse models, inhibitory targeting of myeloid cell surface receptors (PD-L1, CD47/SIRP1α, CCR2, CSF1R, and integrin α4β1), signaling components (PI3Kγ, mTORC1, BTK, and PDE5), transcription factors (KLF6, STAT3, TWIST, ZEB1, and NFAT1), metabolic pathways (arginine metabolism), and others, can prevent tumor immunosuppression and synergize with immune checkpoint inhibitors to improve antitumor responses. Epigenetic regulation of macrophage polarization – as with Class IIa HDAC inhibitors – may protect from cancer immunosuppression by stimulating macrophage proinflammatory gene expression, and thus activating cytotoxic T cell antitumor responses. Antagonists of several targets, including CSF1R, CCR2, CD47/SIRP1a, PI3Kγ, BTK, and HDACs, as well as agonists of TLRs are currently under clinical investigation as putative cancer therapies for various malignancies.